2018
DOI: 10.1080/00220388.2018.1502877
|View full text |Cite
|
Sign up to set email alerts
|

Does the Increase in Competition between Schools Improve the Quality of the Service? The Role of Educational Reform in Chile

Abstract: We analyse the effect of geographic competition between schools on academic performance in Chile. The analysis controls for prior pupil performance, and a range of school and municipality characteristics. We allow for the endogeneity of voucher school location, using the number of local Catholic churches as an instrument. We find that a larger number of public schools positively affects the quality of education of other schools located in the same area, particularly amongst middle-class families and in middle-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Holding the student constant as the school sector changed, this study reported a positive but small and not always significant effect of private voucher schools on test scores (0.05 SD). Other researchers trying to compare the effects of Chile’s public and private schools have relied on instrumental variables such as the density of population (Auguste and Valenzuela 2004) or the density of Catholic churches and clergy (Cartagena Farias and McIntosh 2019; Gallego 2013), but these instruments are unconvincing, especially because most private schools in Chile are not Catholic today.…”
Section: School Choicementioning
confidence: 99%
“…Holding the student constant as the school sector changed, this study reported a positive but small and not always significant effect of private voucher schools on test scores (0.05 SD). Other researchers trying to compare the effects of Chile’s public and private schools have relied on instrumental variables such as the density of population (Auguste and Valenzuela 2004) or the density of Catholic churches and clergy (Cartagena Farias and McIntosh 2019; Gallego 2013), but these instruments are unconvincing, especially because most private schools in Chile are not Catholic today.…”
Section: School Choicementioning
confidence: 99%